2007
DOI: 10.2752/175183407x249658
|View full text |Cite
|
Sign up to set email alerts
|

Holy pleather: materializing authority in contemporary orthodox jewish publishing

Abstract: ArtScroll-a major contemporary Orthodox Jewish publishing house based in Brooklyn, New York-offers a compelling case for studying the roie of materiality in religious print culture. This essay draws upon actor-network theory to examine the "material agency" of key ArtScroll publications, such as prayer books. Bibles, and cookbooks, showing how these artifacts play an active roie within various arenas of Jewish social life, from public prayer to domestic display to kitchen labor. By focusing on the role of book… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…A shift of focus that has occurred in scholarly work on religion lately, and which also can be observed in the study of religious authority, can be found in the increased emphasis on aesthetic, sensorial, bodily and material dimensions (Meyer 2009(Meyer , 2010Schulz 2006;Stolow 2005Stolow , 2007. Such a focus also turns out to be fruitful when it comes to analysing the changing role of the maddāhān in Iran.…”
Section: Madāhān In a Changing Landscape Of Islamic Authoritymentioning
confidence: 98%
“…A shift of focus that has occurred in scholarly work on religion lately, and which also can be observed in the study of religious authority, can be found in the increased emphasis on aesthetic, sensorial, bodily and material dimensions (Meyer 2009(Meyer , 2010Schulz 2006;Stolow 2005Stolow , 2007. Such a focus also turns out to be fruitful when it comes to analysing the changing role of the maddāhān in Iran.…”
Section: Madāhān In a Changing Landscape Of Islamic Authoritymentioning
confidence: 98%
“…A shift of focus that has occurred in scholarly work on religion lately, and which also can be observed in the study of religious authority, can be found in the increased emphasis on aesthetic, sensorial, bodily and material dimensions (Meyer 2009(Meyer , 2010Schulz 2006;Stolow 2005Stolow , 2007. Such a focus also turns out to be fruitful when it comes to analysing the changing role of the maddāhān in Iran.…”
Section: Madāhān In a Changing Landscape Of Islamic Authoritymentioning
confidence: 98%
“…But it is worth mentioning that it has been a focus of significant scholarly attention, particularly in the study of Jewish homes, Jewish religiosity, cultural transmission, and daily life. Among many authors: A, 2018; Ochs 1999, 2010; Mann 2022; Stolow 2007.…”
mentioning
confidence: 99%